Comparative study of clinic-microbiological profile of fungal and bacterial sepsis in neonates - Sharma, Shruti; Karnawat, B. S.; Gupta, Shrey (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal sepsis both bacterial and fungal sepsis is a major cause of neonatal mortality in India. This study is an attempt at determining the spectrum of fungal and bacterial infections in our NICU and ways to differentiate fungal from bacterial sepsis. Methods: All culture positive cases of bacterial and fungal sepsis from neonates in nursery of JLN hospital Ajmer from November 2016 to November 2017 were included in the study. The bacterial and fungal cases were compared for clinical and laboratory features, complications and outcome. Chi square test was used. Results: Culture positive sepsis was found in 391 cases out of total 2190 cases (17.8%) out of which 84.9% were bacterial (EONS 30% and LONS 70%) and 15.1% fungal (EONS 33.8% and LONS 66.1%). Fungal sepsis was found more in lower gestational age (55.9% versus 31.3%; p value 0.003) and in lower birth weight babies (76.2% versus 62.9%; p-value 0.004). Mortality rate was higher in fungal group (40% versus 19.5%; p-value: 0.0003). WBC count of <5000, platelet count <1.5 lac, reactive CRP, hyperglycemia, NEC, ventilation was significantly higher in fungal sepsis. While meconium stained liquor, per vaginal exams >3, maternal fever, mode of delivery, hypoglycemia, increased serum creatinine, respiratory distress, deranged CRT, temperature instability, intra cranial haemorrhage and length of hospital stay were found to be insignificant. Conclusions: In this study fungal sepsis when compared with bacterial sepsis, was found to be associated more with complications and mortality.